Short-term exposure to ambient particulate matter and outpatient visits for respiratory diseases among children: A time-series study in five Chinese cities. (January 2021) - Li, Meng; Tang, Jie; Yang, Huihua; Zhao, Lei; Liu, Ya; Xu, Haoli; Fan, Yali; Hong, Jun; Long, Zhen; Li, Xiaojuan; Zhang, Jianduan; Guo, Wenting; et al.
Abstract: There was limited evidence regarding the association between short-term exposure to ambient particulate matter (PM) and respiratory outpatient visits among children at a multicity level. In this study, a time-series study was conducted among children aged 0–14 years in five Chinese cities from 2013 to 2018. City-specific effects of fine particles (PM2.5 ), inhalable particles (PM10 ) and coarse particles (PM10-2.5 ) were estimated for time lags of zero up to seven previous days using the overdispersed generalized additive models after adjusting for time trends, meteorological variables, day of the week and holidays. Meta-analyses were applied to pool the overall effects, while the exposure-response (E-R) curves were evaluated using a cubic regression spline. The overall effects of PM were significantly associated with total and cause-specific respiratory outpatients among children, even at PM2.5 and PM10 levels below the current Chinese Ambient Air Quality Standards (CAAQS) Grade II. Each 10 μg/m 3 increment in PM2.5, PM10 and PM10-2.5 at lag 07 was associated with a 1.39% (95% CI: 0.38%, 2.40%), 1.10% (95% CI: 0.38%, 1.83%) and 2.93% (95% CI: 1.05%, 4.84%) increase in total respiratory outpatients, respectively. An E-R relationship was observed except for PM2.5 in Beijing and PM10 and PM10-2.5 in Shanghai. The effects of PM were stronger in cold season in 3 southern cities, while it was stronger in transition season in 2 northern cities. In conclusion, short-term PM exposures were dose-responsive associated with increased respiratory outpatient visits among children, even for PM2.5 and PM10 levels below current CAAQS II in certain cities. Highlights: PM exposure was dose-responsive associated with respiratory outpatients among children. PM effects exist even at PM2.5 and PM10 levels below the CAAQS II. PM effect was stronger in cold season in southern cities but stronger in transition season in northern cities. There were no significant differences in age, sex and specific respiratory subgroups.